Factors driving intraspecific diversity in mono-species and mixed-species biofilm - Nai, Jia Wen (2017)
Diversity has long been recognized to play an essential role in ensuring the survival of biological communities. In particular for sessile communities such as biofilms, both intraspecific (genotypic) and interspecific (species) diversities can have significant effects on the fitness of the community under unfavourable conditions such as oxidative stress and starvation. In this project, we explored the effects of nutrients (casamino acids, glucose and fumarate) and quorum sensing (QS) on the interspecific and intraspecific diversities of Pseudomonas protegens mono-species biofilms and Pseudomonas aeruginosa, P. protegens and Klebsiella pneumoniae mixed-species biofilms. Biofilms were cultivated in three-channel flow cells for 6 days and their morphotypic variants were enumerated from days 3 to 6 based on their differences in colony morphologies as compared to the wild type. Our results suggest that casamino acids promote the formation of P. protegens variants in both mono-species and mixed-species biofilms and each of the four P. protegens variants are dominant and have varying finesses in different carbon sources. Our data also demonstrated that las and rhl QS systems do not influence the production of variants.